Mengenalpasti gaya dan keberkesanan kepimpinan pengetua cemerlang kanan wanita di sekolah : satu kajian kes di sekolah menengah di Tun Abang Haji Openg, Kuching, Negeri Sarawak - Suffian, bin Haji Jalet (Universiti Malaysia Sarawak, (UNIMAS), 2009)
Society places high expectation on schools to produce knowledgeable, morally outstanding and highly-skilled citizens. In order to do so, school principals are expected to lead the school effectively. However, there are discrepancies in the quality of our school leadership. General aim of this study is to identify the style and effectiveness of the school principal leadership and the specific objective is to ascertain the effectiveness of leadership styles used by an excellent senior principal of the school.